Changes on Perception of Ethnic Identity after the End of Mass Migration. The Basques in the United States - Óscar Álvarez Gila (Amnis)
One of the results of several decades of mass migration from Europe to America in the 19th and 20th centuries was the creation of ethnic "communities" in the host countries, composed by the immigrants themselves and their descendants. Even though early theories that proposed the idea of American society as a melting-pot in which all Old-World identities will merge and disappear, the strongest of these identities have reached the present throughout generations, even after the waves of mass migration declined and almost vanished. Nonetheless, the ethnic identities of today are not the same of these of the times when immigration was at his peak. Using the example of Basque immigrants in the USA, we will try to analyze a) the evolution of their ethnic and national identities, b) the elements (including economic, social, cultural and religious aspects) that composed them and the way they changed after the new American-born generations started ruling the ethnic institutions, and c) the emergence of a new "diasporic" identity in which the relationship with the Old Country in Europe is redefined.